Prognostic factors for outcome of microvascular decompression in trigeminal neuralgia: A prospective systematic study using independent assessors. (February 2019) - Heinskou, Tone Bruvik; Rochat, Per; Maarbjerg, Stine; Wolfram, Frauke; Brennum, Jannick; Olesen, Jes; Bendtsen, Lars
Introduction: There is a lack of high-quality prospective, systematic studies using independent assessors of outcome of microvascular decompression as treatment for trigeminal neuralgia. Methods: Clinical characteristics and outcome data were recorded prospectively from consecutive classical trigeminal neuralgia patients, using standardized interviews. Degree of neurovascular contact was evaluated by a 3.0 Tesla MRI blinded to symptomatic side. Patients were assessed before and 12 months after surgery by a neurologist. Results: Twenty-six men and 33 women completed 12 months follow-up. Forty-one patients (69%) had an excellent outcome (no pain, no medication). Ten (18%) patients had a good outcome. Eight (12%) patients had no improvement or had worsening of pain. MRI showed neurovascular contact with morphological changes in 34 patients (58%). Odds ratio between neurovascular contact with morphological changes and excellent outcome was 4.4 (Cl 1.16–16.26), p = 0.029. Odds ratio between male sex and excellent outcome was 11.38 (Cl 2.12–59.52), p = 0.004. No significant association was found between excellent outcome and concomitant persistent pain, current age or disease duration. Conclusion: Neurovascular contact with morphological changes and male sex are positive predictive factors for outcome of microvascular decompression. The findings enable clinicians to better inform patients before surgery.